Rules of Practices: On the Methodology in the Work of Michel Foucault - Urošević, Milan (Etnoantropološki problemi / Issues in Ethnology and Anthropology, 2021)
The subject of this paper is the methodology Michel Foucault used in his work. In the paper we will try to show a continuity in his work through the concept of “rules”. We will examine how Foucault used the notion of rules in the three methodological approaches found in his research. In the first section we will show how he used the notion of rules in his archeological method aimed at researching discursive practices. Then we will examine how he used the notion of rules in his genealogical method through which he combined the research of discursive and non-discursive practices. Lastly we will examine the third period of his work in which he researched the rules for forming subjectivity. In the end we will give a general understanding of Foucault’s methodology in the light of the concept of rules which will be named “interpretative analytics of practice” and then relate it to his understanding of the ontology of those rules. Our paper will be concluded by pointing out some of Foucault’s ideas about a non-scientific role his scientific work should have.